2020
DOI: 10.14202/vetworld.2020.706-715
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and meat characteristics of male Kacang goat fattened by complete silage

Abstract: Aim: The aim of the study was to determine the carcass and meat characteristics of male Kacang goat fattened by complete silage made from natural grass, Sorghum bicolor (L.) Moench and Pennisetum purpuphoides. Materials and Methods: This study examined 12 young male Kacang goats aged 10-12 months with an initial body weight of 10-12 kg. The livestock was divided into three groups randomly to receive feed treatments. The three treatments of this study included T1: Complete silage made from natural gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Kacang goat fed with fermented cocoa shell without an additional starter feed (containing high nutrients) was shown to lower the cholesterol content of the meat [63]. Furthermore, it was found that silage completely from natural grass as feed increased the contents of collagen and cholesterol in goat meat [64]. Interestingly, many functional compounds of goat meat such as taurine, carnosine, coenzyme, Q10, creatine, and creatinine have been identified [65].…”
Section: Nutritional Properties Of Goat and Sheep Meatmentioning
confidence: 99%
“…Kacang goat fed with fermented cocoa shell without an additional starter feed (containing high nutrients) was shown to lower the cholesterol content of the meat [63]. Furthermore, it was found that silage completely from natural grass as feed increased the contents of collagen and cholesterol in goat meat [64]. Interestingly, many functional compounds of goat meat such as taurine, carnosine, coenzyme, Q10, creatine, and creatinine have been identified [65].…”
Section: Nutritional Properties Of Goat and Sheep Meatmentioning
confidence: 99%
“…Non-carcass components consist of blood, head, feet, skin, tail, digestive tract, urinary bladder, heart, trachea, lungs, kidneys, spleen, liver and fat tissue [31,32]. According to studies [33,34] feed can affect the weight gain of non-carcass components. Therefore, goats that consume feed with the same energy will have the same component weight.…”
Section: The Effect Of Treatment On Carcass and Non Carcassmentioning
confidence: 99%
“…Masalah kekurangan pakan adalah hal yang sering terjadi pada kondisi lahan kering seperti di wilayah Provinsi Nusa Tenggara Timur (NTT). Tahuk et al, (2020) menyatakan bahwa pada saat hujan produksi biomasa tanaman pakan melimpah sedangkan pada musim kemarau produksinya menurun tajam. Kondisi tersebut akan berdampak pada produktivitas yang berfluktuatif seiring dengan pergantian musim.…”
Section: Pendahuluanunclassified